Management of Chronic Hepatitis B in Childhood: A Comprehensive Guideline - Rukunuzzaman, Md; Karim, ASM Bazlul; Nurullah, Mohammed; Mazumder, Md Wahiduzzaman; Rahman, Md Atiar; Begum, Fahmida (Bangladesh Journal of Child Health, 2017)
This guideline has been written to make familiar childhood hepatitis B virus (HBV) infection management for the pediatrician of Bangladesh. To develop this guideline, local & international data reviewing and several international practice guideline on the management of HBV infection were searched webs. This guideline has been developed to assist pediatric gastroenterologists, pediatricians and other health care providers for the management of HBV in Bangladesh. Objective of these guidelines is to give updated information in the management of HBV infection. Bangladesh J Child Health 2016; VOL 40 (2) :103-114